Interdisciplinarity in the teaching of Mathematics in Basic Education (Research, Society and Development, 2022)
This article is an integrative review research of an exploratory nature, which aims to gather and analyze studies on interdisciplinary teaching in the discipline of mathematics, in addition to revealing the perspective of teachers and researchers of basic education in relation to interdisciplinarity and presenting the main difficulties surrounding its practice. It is considered that the mathematics curriculum component causes disinterest or is considered difficult by many students. Therefore, it is necessary to think of solutions as interdisciplinary strategies in classes. With this, we sought to reveal whether it is possible to develop interdisciplinary classes in the discipline of mathematics, contributing to learning in basic education. For this, a survey of relevant works that deal with interdisciplinarity and teaching in the area was carried out. As this is an exploratory research, which intends to approach knowledge obtained by other authors on the subject, publications from the last 7 years were sought on the CAPES and Google Scholar platforms. This research started from the combination of the words “interdisciplinarity”, “mathematics”, “teaching” and “basic education”. Of this total, 10 articles were selected that presented content related to the research objectives, which were analyzed and arranged in tables for a better understanding.